Successful transcatheter mitral valve replacement in a patient with bioprosthetic valvular degeneration and severe regurgitation - Çakal, Beytullah; Çakal, Sinem Deniz; Karaca, İbrahim Oğuz; Omaygenç, Mehmet Onur; Yıldırım, Aydın (Turkish Society of Cardiology, 2019)
The implantation of aortic transcatheter heart valves has been successfully performed throughout the world in hundreds of patients with severe dysfunction of a degenerated mitral bioprosthesis or those at high surgical risk for re-operation. The transseptal approach may be more technically challenging, but is a less invasive procedure and may have a lower mortality rate compared with a transapical approach, and also offers a quick patient recovery. This report is a description of a rare case in Turkey: a successful transseptal mitral valve replacement in a case of a failed bioprosthetic valve. This case illustrates the feasibility and safety of percutaneous valve-in-valve implantation to treat a degenerated bioprosthesis.

Transkateter aort kapak, dejenere mitral biyoprotez kapak işlev bozukluğu olan ve tekrar ameliyat riski yüksek olgularda dünyada yüzlerce hastada başarılı bir şekilde kullanılmıştır. Transseptal yaklaşım teknik olarak daha zor olsa da transapikal yaklaşıma kıyasla daha az invaziv, muhtemel daha düşük mortaliteye sahip olup hastanın daha hızlı toparlanması ile ilişkilidir. Burada, dejenere biyoprotez kapağa sahip bir olguda transseptal yaklaşımla başarılı mitral kapak değişimini anlatan ülkemizdeki nadir uygulanmış olan olguyu bildiriyoruz. Bu yazıda, dejenere biyoprotez mitral kapak varlığında güvenli ve etkin bir şekilde perkütan kapak içi kapak implantasyonundan bahsedilmiştir.
Biyoprotez kapak dejenerasyonu ve ciddi yetersizliği olan bir hastada başarılı transkateter mitral kapak replasmanı
WOS: 000464336000011
PubMed ID: 30982818
Keywords: Mitral Regurgitation; Mitral Valve-In-Valve; Mitral Valve Replacement; Transcatheter Valve Replacement; Mitral Yetersizliği; Mitral Valve-In Valve; Mitral Kapak Replasmanı; Transkateter Kapak Replasmanı